Integrated Crop‐Livestock Systems and Water Quality in the Northern Great Plains: Review of Current Practices and Future Research Needs. Issue 1 (1st January 2018) - Faust, Derek R.; Kumar, Sandeep; Archer, David W.; Hendrickson, John R.; Kronberg, Scott L.; Liebig, Mark A.
Abstract : Integrated crop‐livestock systems hold potential to achieve environmentally sustainable production of crop and livestock products. Although previous studies suggest that integrated crop‐livestock systems improve soil health, impacts of integrated crop‐livestock systems on water quality and aquatic ecosystems are largely unknown. This review (i) summarizes studies examining surface water quality and soil leachate for management practices commonly used in integrated crop‐livestock systems (e.g., no‐till, cover crops, livestock grazing) with emphasis on the Northern Great Plains ecoregion of North America, (ii) quantifies management system effects on nutrient and total suspended solids concentrations and loads, and (iii) identifies information gaps regarding water quality associated with integrated crop‐livestock systems and research needs in this area. In general, management practices used in integrated crop‐livestock systems reduced losses of total suspended solids, nitrogen (N), and phosphorus (P) in surface runoff and soil leachate. However, certain management practices (e.g., no‐till or reduced tillage) reduced losses of total N (relative median change = −65%), whereas soluble P losses in runoff increased (57%). Conversely, practices such as grazing increased median total suspended solids (22%), nitrate (45%), total N (85%), and total P (25%) concentrations and loads in surface runoff and aquatic ecosystems. An improved understanding of the interactive effects of integrated crop‐livestock management practices on surface water quality and soil leachate under current and future climate scenarios is urgently needed. To close this knowledge gap, future studies should focus on determining concentrations and loads of total suspended solids, N, P, and organic carbon in runoff and soil leachate from integrated crop‐livestock systems. Core Ideas: Integrated crop‐livestock (ICL) systems may improve agricultural sustainability. Water quality outcomes from ICL systems, however, are largely undocumented. Published research on effects of ICL systems on water quality was reviewed. ICL management practices generally reduced losses of suspended solids and nutrients. Greater emphasis should be placed on collection of water quality data in ICL systems.